2012
DOI: 10.1186/1471-2148-12-43
|View full text |Cite
|
Sign up to set email alerts
|

Sex enhances adaptation by unlinking beneficial from detrimental mutations in experimental yeast populations

Abstract: BackgroundThe maintenance of sexuality is a classic problem in evolutionary biology because it is a less efficient mode of reproduction compared with asexuality; however, many organisms are sexual. Theoretical work suggests sex facilitates natural selection, and experimental data support this. However, there are fewer experimental studies that have attempted to determine the mechanisms underlying the advantage of sex. Two main classes of hypotheses have been proposed to explain its advantage: detrimental mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
50
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 46 publications
1
50
0
Order By: Relevance
“…Although asexual strains achieve higher laboratory fitness [15], they seem not to persist or undergo frequent cladogenesis. Sex may increase the rate of adaptation to novel environments and help purge deleterious alleles [16,17]. Thus, most yeast clades harbor at least some sexual taxa, which likely reflect their ancestral states.…”
Section: Yeast Mating Systemsmentioning
confidence: 99%
“…Although asexual strains achieve higher laboratory fitness [15], they seem not to persist or undergo frequent cladogenesis. Sex may increase the rate of adaptation to novel environments and help purge deleterious alleles [16,17]. Thus, most yeast clades harbor at least some sexual taxa, which likely reflect their ancestral states.…”
Section: Yeast Mating Systemsmentioning
confidence: 99%
“…Furthermore, it can break down negative linkage that builds up in finite populations under selection (16), indirectly favoring more genetic mixing (17,18). Experimental studies have demonstrated that populations with sex adapt faster than asexual ones (19)(20)(21)(22). Furthermore, experimental evolution studies focusing on the within-population evolution of sex (12), as well as of recombination (23) and selfing (24), support the theory that genetic mixing is favorable during adaptation.…”
mentioning
confidence: 91%
“…It is likely that the different outcomes of the abovementioned reports on evolutionary benefits of natural transformation are due to species-specific differences in the selective forces maintaining natural transformation and/or variation in the experimental setups. Recent experimental evidence suggests conditional benefits of recombination as demonstrated under stressful growth conditions in sexually reproducing yeast (Gray and Goddard, 2012), and recently for S. pneumoniae where periods of stress offset the initial costs of competence (Engelmoer et al, 2013).…”
Section: Introductionmentioning
confidence: 97%